Echoendoscopy with elastography in mediastinal lymph nodes - Colaiacovo,Rogerio (2019)
ABSTRACT Elastography is a widely used procedure in conventional ultrasonography that has recently been incorporated in echoendoscopy. This is an innovative and promising technology that aims to increase the negative predictive value of endoscopic ultrasonography and fine-needle aspiration punctures. It is useful for directing punctures in suspect areas and, consequently, improves diagnostic performance. This is a non-invasive technique, easy to perform, without additional costs or complications. The main indications are the analysis of solid pancreatic masses, lymph nodes, subepithelial lesions, lesions in the left hepatic lobe and in the left adrenal. Negative or inconclusive cases of fine-needle aspiration can be submitted to elastography when there is a strong suspicion of malignancy. Elastography has a high precision for the differential diagnosis of solid masses and in difficult-to-access anatomic sites, as well as in mediastinal lymph nodes and pancreatic tumors. The procedure is based on the degree of tissue elasticity measurement, with a good correlation between the elasticity index and histopathological features. We report the case of four patients evaluated by echoendoscopy and qualitative elastography who had differential diagnoses in mediastinal lymph nodes: sarcoidosis, lymphoma, histoplasmosis and esophageal neoplasia.